2003
DOI: 10.1046/j.1365-2095.2003.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary vitamin E and C level on market-size turbot (Scophthalmus maximus ) fillet quality

Abstract: Fish fillet quality has been shown to be influenced by the level of antioxidants in preslaughter diet. Thus, an experiment was conducted to study the effect of different levels of vitamin E and C on the fillet quality of market-size reared turbot (Scophthalmus maximus). Turbot of a mean initial weight of 347 ± 20 g were divided into four groups and fed commercial turbot diets (60% protein, 12% fat), supplemented with a-tocopheryl acetate (mg kg )1 ) and ascorbyl-2 monophosphate (mg kg )1 ) at the following die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 23 publications
7
55
1
6
Order By: Relevance
“…Yildiz (2004) proved that the fillet Vitamin-E content of the fish reflected their dietary ATA levels. This positive correlation between dietary and fillet Vitamin-E content is also reported for rainbow trout and other aquaculture species such as Atlantic salmon, sea bass, turbot and Atlantic halibut show comparable results (Bjerkeng et al 1999, Ruff et. al.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Yildiz (2004) proved that the fillet Vitamin-E content of the fish reflected their dietary ATA levels. This positive correlation between dietary and fillet Vitamin-E content is also reported for rainbow trout and other aquaculture species such as Atlantic salmon, sea bass, turbot and Atlantic halibut show comparable results (Bjerkeng et al 1999, Ruff et. al.…”
Section: Discussionsupporting
confidence: 67%
“…Alpha-tocopherol acetate (ATA) is used as a vitamin-E source in fish feed in aquaculture, with the aim of improving fish growth (Hamre et al 1998, Kaushik et al, 1998, Huo et al 1999. The effects of including varying amounts of vitamin-E on the quality of fish fillet has been studied for several species such as Rainbow trout (Boggio et al 1985, Frigg et al 1990, Jensen et al, 1998, Chaiyapechara et al 2003, Channel catfish (Bai and Gatlin 1993), Sea bass , Atlantic salmon (Waagbo et al1993, Hamre et al 1998, Scaife et al 2000, turbot (Ruff et al 2003), Catfish (Lim et al 2001), Nile tilapia (Gammanpila et al 2007), Sunshine bass (Trushenski 1999) and hybrid Tilapia (Huang et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Tocopherols prevent free radical oxidation of lipids and fatty acids in vivo (Bell et al 2000); postslaughter, they can reduce rates of oxidation and lengthen shelf life of fresh or frozen fillets (Gatta et al 2000;Ruff et al 2002;Hamre et al 2004). Tissue a-tocopherol content and oxidative stability have been enhanced via dietary supplementation with SYNE in sunshine bass (Kocabas and Gatlin 1999), rainbow trout Oncorhynchus mykiss (Chaiyapechara et al 2003), European seabass Dicentrarchus labrax (Gatta et al 2000), Atlantic salmon (Hamre et al 1998(Hamre et al , 2004Scaife et al 2000), Atlantic halibut Hippoglossus hippoglossus (Ruff et al 2002(Ruff et al , 2004, and turbot Scophthalmus maximus (Ruff et al 2003(Ruff et al , 2004. Although no significant differences were noted after long-term storage, fillet aldehydes numerically decreased with increasing dietary NSVE but not with ethoxyquin.…”
Section: Discussionmentioning
confidence: 99%
“…Improved product quality has been achieved by feeding on supra-nutritional levels of α-tocopheryl acetate before slaughter (RUFF et al, 2002b). This has been demonstrated by Ruff et al (2003), who suggested supplementation of feeds with at least 550 mg α-tocopheryl acetate kg -1 diet for market size turbot two months prior to slaughter improved fillet quality.…”
Section: Introductionmentioning
confidence: 84%
“…This has been demonstrated by Ruff et al (2003), who suggested supplementation of feeds with at least 550 mg α-tocopheryl acetate kg -1 diet for market size turbot two months prior to slaughter improved fillet quality. Others studies on the Atlantic salmon Salmo salar (ONIBI et al, 1996;, sea bass Dicentrarchus labrax and hybrid tilapia Oreochromis niloticus x O. aureus HZU, 2002) also demonstrated that when dietary vitamin E level increased, lipid peroxidation in post-mortem muscle was inhibited.…”
Section: Introductionmentioning
confidence: 88%